2021
DOI: 10.24002/ijis.v4i1.4727
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Factors of Online Game Acceptance Using Technology Acceptance Model

Abstract: In the last two decades, many companies create online games. Online game is a game that is connected to the internet, where players can play and communicate with other players in different places at the same time. There are many types of game, such as adventure, strategy, cooking, make up, and so on. That is why a lot of people love to play online game. This study tries to identify the factors that support online game acceptance by students of Atma Jaya Yogyakarta University, because many students at this univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
3
5
0
1
Order By: Relevance
“…Furthermore, another factor in the proposed model, based on TAM, was perceived usefulness. Perceived usefulness was one of the determinant variables of intention to use among players according previous studies (Dewi & Natalia, 2021;Kim et al, 2013;Pando-Garcia et al, 2016;Zhu et al, 2012). Furthermore, as again shown by Chauhan et al (2021), the analytics showed that perceived usefulness was a major factor in behavior intention in the online mobile gaming industry.…”
Section: Figure 1 Research Modelsupporting
confidence: 60%
See 4 more Smart Citations
“…Furthermore, another factor in the proposed model, based on TAM, was perceived usefulness. Perceived usefulness was one of the determinant variables of intention to use among players according previous studies (Dewi & Natalia, 2021;Kim et al, 2013;Pando-Garcia et al, 2016;Zhu et al, 2012). Furthermore, as again shown by Chauhan et al (2021), the analytics showed that perceived usefulness was a major factor in behavior intention in the online mobile gaming industry.…”
Section: Figure 1 Research Modelsupporting
confidence: 60%
“…Furthermore, the insignificant effect of perceived ease of use on attitude toward use was against almost all previous studies. As reported by Dewi and Natalia (2021), Sukendro et al (2020), andZhu et al (2012), these studies stated that the relationship existed and significantly had positive effects. However, the effect of perceived ease of use on attitude varies greatly depending on the case, the object studied, and the target population (Indarsin & Ali, 2017).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations